Deteksi mastitis subklinis pada kambing peranakan etawa di hanif fram dusun aik mual timur desa aik mual kecamatan praya kabupaten lombok tengah provinsi nusa tenggara barat - Mardani; Kholik; Dina Oktaviana; Maratun Janah (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
The Etawa crossbred goat is a hybrid goat that plays a strategic role in the Indonesian livestock sector. A cross between the native Etawa goat from India and local Indonesian goats, this species has undergone a historical evolution that reflects the adaptation of modern livestock technology to tropical environments. Mastitis occurs when pathogens enter the udder through the milk ducts, from unhygienic milking processes, or wounds in the udder skin. The main causes are bacteria such as Staphylococcus aureus, Streptococcus spp., or Escherichia coli. The purpose of this study was to determine the detection of subclinical mastitis in Etawa crossbred goats and to determine the California Mastitis Test (CMT) score. It can be concluded that an average of 16 Etawa crossbred goat tail samples (lactaxes) were found to be 14 goat tail samples that were indicated positive for subclinical mastitis, with a detection rate of 87.5%. Subclinical mastitis is caused by several factors, including poor barn management, the age of the lactation and sow, and poor hygiene during milking, which can lead to contamination of healthy goats from sick PE goats.